2010
DOI: 10.1080/15313220.2010.503536
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Using the Electronic Response System in a Large Class

Abstract: Most students come to today's classrooms with technological dependence and a desire for instant gratification. As faculty struggle to engage and teach this generation of students, there is an increase in technology use in classrooms. One tool commonly used to engage these learners is the electronic response system (ERS), which allows students to answer questions anonymously during class and to receive instant feedback. This study examined ERS implications in a large classroom setting within the content area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The literature has suggested that there are reasons to incorporate these devices into the classroom. This study supports the literature and also suggests that clickers in teaching can enhance students' learning engagement in a classroom setting (Chui & Martin, 2013;Espey & Brindle, 2010;Hwang & Wolfe, 2010). Therefore, the practical implication of this study is clear.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The literature has suggested that there are reasons to incorporate these devices into the classroom. This study supports the literature and also suggests that clickers in teaching can enhance students' learning engagement in a classroom setting (Chui & Martin, 2013;Espey & Brindle, 2010;Hwang & Wolfe, 2010). Therefore, the practical implication of this study is clear.…”
Section: Discussionsupporting
confidence: 80%
“…In order for instructors to reach out and facilitate students' understanding of the subject at hand, adopting technology in the classroom is important. Many students today would like to have the option of using technology as part of a lecture (Hwang & Wolfe, 2010). There are many different educational technology solutions to incorporate in the design of a lecture to promote active learning; personal response systems and lecture software applications are two examples.…”
Section: Introductionmentioning
confidence: 99%
“…Instructors can collect student feedback during a class session through the use of SRS (Trees & Jackson, ). Student remotes are small, usually hand‐held devices that allow students to respond to questions posed by the instructor in real time during the class meeting (Hwang & Wolfe, ). While these systems work in varied ways, the systems generally utilize infrared waves, radio waves or a wireless Internet signal (Caldwell, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means that some students are not engaging and communicating with their instructor and therefore missing out on the benefits, such as achieving higher grades, that engagement provides (Rocca, ). SRS are a way for students to anonymously interact with their instructors in the moment without their anxieties inhibiting their responses (Hwang & Wolfe, ). Bruff () explains, ‘the anonymity that clickers provide students can sometimes be used to uncover student perspectives that might not be clear to instructors through other means of assessment’ (p. 41–42).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation